Distance and the Pattern of Intra-European Trade - Beckerman, W. (The Review of Economics and Statistics, 1956)
THE basic question to which this paper is addressed is "What is the importance of distance in determining the pattern of Western European trade?"The importance of distance in the pattern of trade has, of course, always been recognized.The assumption of "no transport costs," which has always been necessary in expositions of theories of international trade, is a recognition of the fact that transport costs, that is, the costs of covering distance, exist and are significant; so that abstraction from them has to be made quite explicitly in order to analyze other elements such as factor endowments.' 0 0 t 0 0 0 "inCq 0 e oo HO , "d0 80 8 00 0 * .. 99"o 'A-.